Semantic segmentation of tumor from 3D Structural MRI using U-Net Autoencoder - Farzana, Maisha; Any, Md. Jahid Hossain (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.